2015
DOI: 10.1093/ntr/ntv239
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Residents’ Attitudes and Satisfaction Before and After Implementation of a Smoke-Free Policy in Boston Multiunit Housing

Abstract: Introduction: In 2012, the Boston Housing Authority (BHA) in Massachusetts implemented a smoke-free policy prohibiting smoking within its residences. We sought to characterize BHA resident experiences before and after the smoke-free policy implementation, and compare them to that of nearby residents of the Cambridge Housing Authority, which had no such policy. Methods: We recruited a convenience sample of nonsmoking residents from the BHA and Cambridge Housing Authority. We measured residents' awareness and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 14 publications
6
25
0
Order By: Relevance
“…Higher education is also associated with increased likelihood of owning a home, which may explain the higher smoking bans among adults living in single‐family homes (Malito, 2017). People living in multifamily buildings may experience a lack of compliance with and enforcement of smoke‐free policies among residents (Rokicki et al., 2016) which may increase their risk of second‐hand smoke exposure. Among study participants, current smokers and those who quit since the outbreak had a significantly lower rate of indoor smoking bans than nonsmokers.…”
Section: Discussionmentioning
confidence: 99%
“…Higher education is also associated with increased likelihood of owning a home, which may explain the higher smoking bans among adults living in single‐family homes (Malito, 2017). People living in multifamily buildings may experience a lack of compliance with and enforcement of smoke‐free policies among residents (Rokicki et al., 2016) which may increase their risk of second‐hand smoke exposure. Among study participants, current smokers and those who quit since the outbreak had a significantly lower rate of indoor smoking bans than nonsmokers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in 2012, the Boston Housing Authority (BHA) implemented a SFH policy that was similar to HUD’s. In a post implementation assessment, 51% of BHA respondents indicated that other residents “never” or “rarely” followed the new SFH policy, and 41% of respondents were dissatisfied with policy enforcement [ 15 , 16 ]. In a qualitative assessment of the BHA policy, a lack of outdoor smoking areas was cited by residents as one of the “greatest challenges to compliance” [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…1011 Residents with lower education and socioeconomic status were less likely to favor smoke-free public housing, even though substantial proportions are known to experience SHS incursions in MUH environments. 10 Current cigarette smokers, who comprise one-third of HUD-assisted adults, 12 were also less likely to favor the rule than never smokers.…”
Section: Discussionmentioning
confidence: 99%